The Culture of Cooperation as a Condition of Shaping a Party Leader - Atikyan, Mane (YSU Journal of International Affairs, 2023)
The article makes a focus on the value multidimensionality of the culture of cooperation. The author justifies an approach according to which the culture of cooperation is such a system of relations that includes the processes of civil solidarity and agreement, the development of the culture of state-building, and the provision of national security. In this context, the author emphasizes adaptability and discusses mutually beneficial cooperation as a driving force for the establishment of party leadership in the context of modern information and communication development. According to the author, cooperation is a mutually beneficial cooperative communication between agile and competent political actors to ensure effective governance and innovation through the compromise policies of mutual security. At the same time, the author argues that the transformation of the political system in Armenia takes place in the complex process of establishment of the leadership institute. Being the most important direction of the activity of the party leaders, the identification of this problem was and remains a component of the development of the culture of cooperation in Armenia. From this point of view, it is recommended to increase the level of political consciousness of the population to ensure the optimality of the party’s activity, reducing marginalism and implementing lasting socialization. Obviously, in the conditions of implementing the RA public policy, it is necessary to consider the party leader as an innovative actor of the cooperative culture because the party activists who come to the parliament through the elections and receive the status of a certain leader in the executive power are responsible for maintaining coexistence and ensuring the result. At the same time, the existence of a cooperative culture in the process of transformation of the democratization of Armenia will enable to increase the level of legal and political awareness of party leaders, the propensity for innovation, as well as the responsibility of ensuring the supremacy of public interest in the decision-making process.
Keywords: transforming society; culture of cooperation; party leader; civil solidarity; state-building culture; national security; result management; responsibility